2008
DOI: 10.1149/1.2928612
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Oxygen Surface Exchange at the Hetero-interface of (La,Sr)CoO[sub 3]/(La,Sr)[sub 2]CoO[sub 4] with PLD-Layered Films

Abstract: The preferential site for oxygen isotope exchange was investigated on layered films of La 2−x Sr x CoO 4 ͑x = 0.5,1.0͒/La 0.6 Sr 0.4 CoO 3 prepared by pulsed laser deposition ͑PLD͒ on a polycrystalline Ce 0.9 Gd 0.1 O 1.95 . An isotope exchange experiment was performed at 773 K in 18 O-enriched oxygen of 0.2 ϫ 10 5 Pa. Three-dimensional imaging of secondary ion mass spectrometry ͑SIMS͒ was carried out to visualize the isotope distribution. The SIMS images suggested that there are fast oxygenincorporation paths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
122
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 26 publications
5
122
0
Order By: Relevance
“…This effect was found by Sase as the enhancement of oxygen decomposition reaction on perovskite-type La 1¹x Sr x CoO 3 oxide electrode surface with the dispersion of La 2¹y Sr y CoO 4 phase on it and detailed analysis was reported. 52,53,56 Conceptually similar effect was already employed by many researchers such as GDC anode dispersed with Ni.…”
Section: Response Of Potentiometric Sensor and Chemical Capacitancementioning
confidence: 73%
See 1 more Smart Citation
“…This effect was found by Sase as the enhancement of oxygen decomposition reaction on perovskite-type La 1¹x Sr x CoO 3 oxide electrode surface with the dispersion of La 2¹y Sr y CoO 4 phase on it and detailed analysis was reported. 52,53,56 Conceptually similar effect was already employed by many researchers such as GDC anode dispersed with Ni.…”
Section: Response Of Potentiometric Sensor and Chemical Capacitancementioning
confidence: 73%
“…42,51 The enhancement of surface reaction of La 1¹x Sr x CoO 3¹D by the dispersion of La 2¹x Sr x CoO 4 was confirmed by SIMS. 52,53 Using tracers and SIMS analysis after quenching, we can visualize the reaction path three dimensionally.…”
Section: Semi In-situ Measurements; Application Of Simsmentioning
confidence: 99%
“…[13][14][15][16][17][18] Using well-defined epitaxial thin film systems, remarkably enhanced oxygen surface exchange kinetics (up to ∼2 orders of magnitude) of LSC 113 has been reported by decorating (La 0.5 Sr 0.5 ) 2 CoO 4±δ (LSC 214 ) phase on the LSC 113 surface. [13,19] Coherent Bragg rod analysis (COBRA) and density functional theory (DFT) have suggested that the enhanced oxygen surface exchange kinetics may be attributed to the Sr segregation at the LSC 214 -LSC 113 interface and the LSC 214 surface, resulting from a large driving force for A-site cation interdiffusion across the heterostructured interface.…”
Section: Introductionmentioning
confidence: 99%
“…6 Some interfaces in oxides are known to enhance ionic diffusion. [7][8][9] Modifications of interfacial charge to manipulate properties of the space charge layer provide another venue of changing transport properties in the proximity of an interface. If the density of the interfaces is such that space charge layers overlap, one can expect emergent behavior of ionic transport properties that cannot be interpolated from the bulk counterpart behavior.…”
mentioning
confidence: 99%